Pengaruh Substitusi Tepung Ubi Jalar Oranye (IpomoeaBatatas L.) Terhadap Kadar Betakarote - Belaoka, Pramudya Kurnia, STP, MAgr, Endang Nur W, S.St., M.Si.Med (2016)
Introduction: Deficiency of vitamin A is one of the main nutritional problem in Indonesia. Vegetable foodstuffs which contain provitamin A is the orange-fleshed sweet potato. Substitusion can help improve the nutritional value, including betacarotene. Proximat analysis needs to be done to determine changes in the nutritional value due to the substitution of orange-fleshed sweet potato flour. Objective: The purpose of the research was to determine the Subsititution Effect of orange-fleshed sweet potato flour (lpomoea batatas L.) in value of betacarotene and proximate composition in biscuit. Methode: The design of the research used an experimental design with a completely randomized design (CRD) with 4 treatments and 1 control with 2 replications. It's substitution of orange-fleshed sweet potato flour was 0%, 40%, 50%, and 60%. The value of beta-caroten obtained by the method of thin layer chromatography (TLC) and proximate value analysis using "one way ANOVA" test with a significant level of 95% and continued by duncan multiple range test (DMRT). Result: Value of beta-caroten in biscuit substitused orange-fleshed sweet potato flour 0%, 40%, 50%, and 60% were <62,9 mg/kg. The highest of water content was 4,58% and the lowest was 3,68%. The highest of ash content was 1,6% and the lowest was 1,06%. The highest of protein content was 8.82% and the lowest was 4,85%. Then, the highest of carbohydrate content was 71,4% and the lowest was 67,1%. Conclusion: There is a substitution effect against the orange sweet potato flour for biscuits proximate with value sig. = 0.00 (p <0.05). Suggestion: before the addition of orange-fleshed sweet potato flour with the greater ranges to increase the value of beta-caroten.